2014
DOI: 10.4254/wjh.v6.i10.716
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the insulin-like growth factor pathway in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the third leading cause of cancer-related deaths worldwide. Only 30%-40% of the patients with HCC are eligible for curative treatments, which include surgical resection as the first option, liver transplantation and percutaneous ablation. Unfortunately, there is a high frequency of tumor recurrence after surgical resection and most HCC seem resistant to conventional chemotherapy and radiotherapy. Sorafenib, a multi-tyrosine kinase inhibitor, is the only chemotherapeutic option… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 230 publications
0
58
0
Order By: Relevance
“…Healthy mature hepatocytes do not express IGFIR 16. In HCC samples, up‐regulation of IGFIR is one of the most common alterations, occurring in 30% of patients 33.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Healthy mature hepatocytes do not express IGFIR 16. In HCC samples, up‐regulation of IGFIR is one of the most common alterations, occurring in 30% of patients 33.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo , A12 delayed tumor growth and prolonged survival, reducing proliferation rates and inducing apoptosis 14. Although several IGF1R inhibitors or blocking antibodies have been tested in preclinical models or clinical trials for patients with HCC,9, 14, 15, 16 none has been approved by the FDA, possibly because inhibition of IGF1R alone may not be sufficient to effectively inhibit HCC cell growth and survival. Our data support this hypothesis as inhibition of IGF1R by shRNA or ceritinib has only a modest suppression on HCC proliferation and survival (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors used BI836845, a monoclonal antibody directed against the ligand IGF2, to decrease IGF2/IG1R pathway activation and, consequently, decrease tumor formation in this mouse model. However, toxicity as severe hypoglycemia has limited the use of other IGF inhibitors in clinical trials [13]. The authors concluded that if this monoclonal antibody targeting IGF2 showed no limiting toxicity, it could be tested for treating patients with HCC harboring IGF pathway activation.…”
Section: Budhu Et Al (A High-throughput Screen Identifies Wnt-beta-cmentioning
confidence: 97%
“…Another RTK ligand playing an important role in hypoxia-induced tumorigenesis is insulinlike growth factor 2 (IGF2), which exerts its biologic activity via binding to the insulin-like growth factor 1 receptor (IGF1R) tyrosine kinase [39]. Activation of IGF1R in tumors is very rarely caused by gene amplification or point mutations.…”
Section: Induction Of Rtk Ligandsmentioning
confidence: 99%